Impact of Nursing Interventions on Physical Recovery of Disaster Victims: A Scoping Review - Wiguna, Yutika; Purwandi, Purwandi; Hartati, Tita; Satrio, Rizki Juniar Eko; Utami, Nisa; Sijabat, Pasuria Br; Indriati, Ririn; Trisyani, Yanny (Sekolah Tinggi Ilmu Kesehatan Kendal, 2025)
Disasters, whether natural or human-induced, frequently lead to significant physical injuries and complex health conditions among affected populations. In such contexts, nurses serve as frontline responders who deliver critical care aimed at promoting physical recovery and preventing further complications. This scoping review explores and synthesizes existing literature on the impact of nursing interventions on the physical recovery of disaster victims. The review was conducted in accordance with the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) guidelines. A systematic search was carried out in three major electronic databases PubMed, Scopus, and Web of Science targeting articles published between 2015 and 2025. The following Boolean search string was used: ((disasters) OR (